Analysis of the causes of anxiety in using the English language among form four students / Hanimarlia Hassan - Hassan, Hanimarlia (2010)
This research was conducted to analyze the causes of anxiety of Form Four students of SMK Tun Tuah. A total of 100 students were involved as respondents of the research. Students’ language anxiety was measured using an English Language Anxiety Scale (ELAS) questionnaire, which was developed from the Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire (Horwitz, Horwitz & Cope, 1986). The research findings showed that most of the students experienced a great deal of anxiety when they used the target language in the classroom. From the three subscales of communication apprehension, fear of negative evaluation and test anxiety, it is known that the causes of students’ anxiety were among all derived from negative self perception, fear of peer or language teacher’s evaluations and the fear of failure in taking English tests. It was also found that there is a significant relationship between the causes of anxiety and the students’ English language grades. From the findings, the researcher has come out with a few pedagogical implications for English language teachers to alleviate the students’ anxiety level whenever they use English language in the classroom.